Global shadows : Africa in the neoliberal world order - Ferguson, James, 1959- (Durham [N.C.] : Duke University Press, 2006)
"Both on the continent and off, "Africa" is spoken of in terms of crisis: as a place of failure and seemingly insurmountable problems, as a moral challenge to the international community. What, though, is really at stake in discussions about Africa, its problems, and its place in the world? And what should be the response of those scholars who have sought to understand not the "Africa" portrayed in broad strokes in journalistic accounts and policy papers but rather specific places and social realities within Africa? In "Global Shadows", the renowned anthropologist James Ferguson moves beyond the traditional anthropological focus on local communities to explore more general questions about Africa and its place in the contemporary world. Ferguson develops his argument through a series of provocative essays which open - as he shows they necessarily must - into interrogations of globalization, modernity, worldwide inequality, and social justice. He maintains that Africans in a variety of different social and geographical locations increasingly seek to make claims of membership within a global community, claims that contest the marginalization that has so far been the principal fruit of "globalization" for Africa. Ferguson contends that such claims demand new understandings of the global centred less on trans-national flows and images of unfettered connection than on the social relations that selectively constitute global society and on the rights and obligations that characterize it. Ferguson points out that anthropologists and others who have refused the category of Africa as empirically problematic have, in their devotion to particularity, allowed themselves to remain bystanders in the broader conversations about Africa. In "Global Shadows", he urges fellow scholars into the arena, encouraging them to find a way to speak beyond the academy about Africa's position within an egregiously imbalanced world order."--Book cover
Introduction: Global shadows : Africa and the world -- Globalizing Africa? : observations from an inconvenient continent -- Paradoxes of sovereignty and independence : "real" and "pseudo-" nation-states and the depoliticization of poverty -- De-moralizing economies : African socialism, scientific capitalism, and the moral politics of structural adjustment -- Transnational topographies of power : beyond "the state" and "civil society" in the study of African politics -- Chrysalis : the life and death of the African renaissance in a Zambian internet magazine -- Of mimicry and membership : Africans and the "new world society" -- Decomposing modernity : history and hierarchy after development -- Governing extraction : new spatializations of order and disorder in neoliberal Africa.
Includes bibliographical references (pages 211-247) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Since 1960; Globalization; Mondialisation; POLITICAL SCIENCE -- International Relations -- General; Economic history; Globalization; International economic relations; Politics and government